Comparison of Pain Management Strategies to Reduce Opioid Use Postoperatively in Free Flap Breast Reconstruction: Pain Catheter versus Nerve Block in Addition to Refinements in the Oral Pain Management Regime - Stefansdottir, Andrea B.; Vieira, Luis; Johnsen, Arni; Isacson, Daniel; Rodriguez, Andres; Mani, Maria (Archives of Plastic Surgery, 2024)
Background Perioperative management in autologous breast reconstruction has gained focus in recent years. This study compares two pain management protocols in patients undergoing abdominal-based free flap breast reconstruction: a past protocol (PP) and a current protocol (CP)—both intended to reduce opioid consumption postoperatively. The PP entails use of a pain catheter in the abdominal wound and the CP consists of an intraoperative nerve block in addition to refinements in the oral pain management. We hypothesize that the CP reduces opioid consumption compared to PP.Methods From December 2017 to January 2020, 102 patients underwent breast reconstruction with an abdominal-based free flap. Two postoperative pain management strategies were used during the period; from December 2017 to September 2018, the PP was used which entailed the use of a pain catheter with ropivacaine applied in the abdominal wound with continuous distribution postoperatively in addition to paracetamol orally and oxycodone orally pro re nata (PRN). From October 2018 to January 2020, the CP was used. This protocol included a combination of intraoperative subfascial nerve block and a postoperative oral pain management regime that consisted of paracetamol, celecoxib, and gabapentin as well as oxycodone PRN.Results The CP group (n = 63) had lower opioid consumption compared to the PP group (n = 39) when examining all aspects of opioid consumption, including daily opioid usage in morphine milligram equivalents and total opioid usage during the stay (p < 0.001). The CP group had shorter length of hospital stay (LOS).Conclusion Introduction of the CP reduced opioid use and LOS was shorter.
Keywords: free flap breast reconstruction; pain management; DIEP